Questions of genre and gender: the private investigator Kinsey Millhone - Cabanilles, Antònia (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper analyzes the self-representation of detective Kinsey Millhone in Sue Grafton’s The Alphabet Series to examine the relation between literary genre and gender when a woman embodies the modern figure of a detective.
Keywords: Sue Grafton; Kinsey Millhone; detective fiction; genre; gender